A survey of the Leptodactylid frogs, genus Eupsophus, in Chile - Cei, José Miguel Alfredo María (1960)
Chilean species of Eupsophus are reviewed. Only three fundamental groups are recognized: grayi-roseus, nodosus-coppingeri, taeniatus. Synonymy of E. kriegi, E. maculatus and E. verrucosus with E. nodosus, and of E. bibroni, E. calcaratus and E. masareyi with E. grayi is demonstrated. Morphological affinities in pectoral girdle, prevomerine teeth and color patterns in Chilean species are analyzed. Secondary sex characters of grayi, nodosus and taeniatus are compared and illustrated. The present distributions of nodosus and taeniatus express their probable position as ancient and formerly widespread forms. Biological affinities between E. taeniatus and Brazilian Thoropa are mentioned. Eupsophus coppingeri and E. roseus are specialized and rare forms, sympatric with grayi and nodosus in the southern Chilean rain forest belt.